The Mouse and the Squirrel - Blyton,Enid; Illustrator, Sylvia Ward (London, Alligator Books, 2001)
winter is coming and mouse needs food to survive the cold weather. Will squirrel lend a hand?
A1 shelf
Keywords: English story book